Study area in the Kitimat Fjord System, British Columbia, Canada, within the territories of the Gitga’at First Nation, Kitasoo First Nation, and Haisla First Nation. - Janie Wray (457395); Eric Keen (11014169); Éadin N. O’Mahony (11014172) (2021)
Center pane : Dots indicate locations of research stations. North to south: Fin Island, Whale Point on Gil Island, and the Wall Islets. Asterisk indicates reference point for fjord position metrics (see main text). Right pane : Dots indicate locations of humpback whale photo-identification events, 2004–2019.